Model pembelajaran online fisika berbasis pemodelan - Hidayatullah, Subhan; Haryadi, Rudi (Academy of Education Journal, 2024)
Education in the discipline of physics has experienced significant changes along with developments in technology and internet access. One of these innovative approaches that is increasingly popular is modeling-based online learning models. This article aims to conduct a comprehensive literature review on modeling-based physics learning models implemented online. This approach emphasizes the use of modeling as one of the main tools to facilitate students' deeper understanding of physics concepts. In order to understand and evaluate its impact, this research adopts a structured approach by combining in-depth research and thorough analysis of this online learning model. The theory underlying this learning model involves the integration of information technology and modeling approaches in physics teaching. Supporting data and evidence were obtained through critical research on the implementation of this model in the context of online physics education. In addition, this research measures its effectiveness using data on students' understanding of physics concepts, student satisfaction questionnaires, and participatory observation. The results of this research indicate that the modeling-based online learning model is effective in increasing students' understanding of physics concepts. In-depth analysis also revealed that this approach provides a more interactive and engaging learning experience for students, which is reflected in high levels of satisfaction. This research confirms the great potential of modeling-based physics online learning models in addressing modern educational challenges. The practical and theoretical implications of these findings pave the way for further developments in online physics education and provide a basis for further research in this area. By integrating modeling in online physics learning, we can create a more dynamic and effective learning experience for students in the digital era.